2018
DOI: 10.5194/hess-2018-553
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

When does vapor pressure deficit drive or reduce evapotranspiration?

Abstract: Increasing vapor pressure deficit (VPD) increases atmospheric demand for water, and vapor pressure deficit is expected to rise with increasing greenhouse gases. While increased evapotranspiration (ET) in response to increased atmospheric demand seems intuitive, plants are capable of reducing ET in response to increased VPD by closing their stomata, in an effort to conserve water. Here we examine which effect dominates response to increasing VPD: atmospheric demand and increases in ET, or plant physiological re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 32 publications
2
34
0
Order By: Relevance
“…This result was confirmed, as J H fluxes did not significantly change with an increase in EVI, whereas J LE increased, suggesting that evapotranspiration and the cooling of leaf and soil surfaces had greater influence on the partitioning of available energy. In contrast, J H increased more at the mesic and xeric sites with increasing VPD, suggesting that drier air increased the sensible heat flux from the surface to the atmosphere (Massmann et al, 2018). Similarly, as VPD increased so did σ at all sites.…”
Section: Discussionmentioning
confidence: 89%
“…This result was confirmed, as J H fluxes did not significantly change with an increase in EVI, whereas J LE increased, suggesting that evapotranspiration and the cooling of leaf and soil surfaces had greater influence on the partitioning of available energy. In contrast, J H increased more at the mesic and xeric sites with increasing VPD, suggesting that drier air increased the sensible heat flux from the surface to the atmosphere (Massmann et al, 2018). Similarly, as VPD increased so did σ at all sites.…”
Section: Discussionmentioning
confidence: 89%
“…Sulman et al () similarly found that observed evaporation in a mixed forest responded to both VPD and soil moisture anomalies with similar magnitudes, but the timescales of VPD response (hours) was much shorter than the soil moisture response (multiple days or weeks). It should be noted that the VPD sensitivity has been found to be variable and species dependent (Hetherington & Woodward, ; Gu et al, ; Merilo et al, ) and that model representations are in disagreement (Massmann et al, ; Zhou et al, ). This calls for a better understanding of the role of VPD on land surface‐atmosphere interaction, in particular during episodes of warm and dry air advection typical for European heat waves.…”
Section: Introductionmentioning
confidence: 99%
“…Although evaluation of water rights and corresponding water withdrawals under drought conditions was beyond the scope of this study, our findings suggest that the conversion to center pivot irrigation could amplify the impacts of reduced precipitation on riparian areas. Additionally, an increasing summer VPD could further increase crop water losses to evapotranspiration (Massmann et al, 2018), potentially exacerbating both the hydrological effect and salinization effect of irrigation conversion (Singh, 2015). We note, however, that climate and river discharge trends were quantified only to be compared with trends observed in riparian wetness over the same period .…”
Section: Discussionmentioning
confidence: 99%